A comparative study of the effects of calcium alginate capsules on self-healing properties of base and SBS modified asphalt mixtures. (18th January 2023) - Zhao, Feiyang; Liu, Quantao; Peng, Zhen; Wang, Huan; Wan, Pei; Ye, Qunshan
Graphical abstract: Highlights: Effects of capsules on self-healing ratios of base and SBS modified asphalt mixtures were studied. Oil release ratios after compaction were 5.7% and 7.0% for base and SBS modified asphalt mixtures. Capsules in SBS modified asphalt concrete released oil more rapidly under loading. Both base and SBS modified asphalts were rejuvenated by the capsules. SBS modified asphalt concrete containing the capsules showed lower healing ratio. Abstract: Calcium alginate capsules can gradually release healing agent and heal cracks in asphalt mixtures under vehicle loading. However, the current research is focusing on how calcium alginate capsules affect the self-healing abilities of base asphalt mixtures. It is still unclear whether calcium alginate capsules can be utilized to rejuvenate and heal SBS modified asphalt mixture. Through a three-point bending (3 PB)-cyclic compression loading-3 PB test, the effects of calcium alginate capsules on the self-healing characteristics of base and SBS modified asphalt mixtures were examined and compared in this study. Fourier transform infrared spectroscopy (FTIR) and dynamic shear rheometer (DSR) tests were conducted on extracted asphalt binders to study the release behaviors of the capsules within different asphalt mixtures and their regeneration effects on the asphalt binders. The findings demonstrate that under cyclic compression loading, calcium alginate capsules can greatly enhance the strength recovery ratios of base and SBS modified asphalt concretes. The capsules in SBS modified asphalt concrete released the oil more rapidly than in base asphalt concrete probably due to the higher mixing temperature. Both the base and SBS modified asphalts can be rejuvenated by the oil released from the capsules. However, SBS modified asphalt concrete containing the capsules showed lower strength recovery ratios than base asphalt concrete due to lower flow ability of SBS modified asphalt and incapacity of the capsules to repair the broken SBS polymer network.